Problemas que dificultan una mejor utilización de la Didáctica de las Ciencias en la formación del profesorado y en la enseñanza secundaria - Carrascosa-Alís, Jaime; Domínguez-Sales, M. Consuelo (Revista Científica, 2017)
Science Education today can be considered as a whole and coherent body of specific knowledge with a "hardcore" in which the most direct issues related to key aspects of teaching and learning can be found. The appropriation of this knowledge by teachers is required in order to move towards a higher quality teaching in the field of the experimental sciences. However, this appropriation is not an easy task and requires overcoming a number of problems which must be taken into account. In this paper, some of these problems are discussed, and some proposals to make progress in solving them are justified.